Perbandingan Leasing Dan Ijarah Dalam Hukum Pembiayaan - Gatot Iriyanto; Cora Elly Noviati; Encik Lukmanul Hakim; Ana Laela Fatikhatul Choiriyah (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
Many people's desires and abilities have private vehicles, motorbikes or cars. So that to meet the needs of the Indonesian people, a new breakthrough has emerged regarding leasing or renting to use goods, which is called leasing, this